Wolbachia pipientis modulates germline stem cells and gene expression associated with ubiquitination and histone lysine trimethylation to rescue fertility defects in Drosophila. - Kagemann, C.H.; Bubnell, J.E.; Colocho, G.M.; Arana, D.C.; Aquadro, C.F. (Genetics, 2025)
Wolbachia pipientis are maternally transmitted endosymbiotic bacteria commonly found in arthropods and nematodes. These bacteria manipulate reproduction of the host to increase their transmission using mechanisms, such as cytoplasmic incompatibility, that favor infected female offspring. The underlying mechanisms of reproductive manipulation by W. pipientis remain unresolved. Interestingly, W. pipientis infection partially rescues female fertility in flies containing hypomorphic mutations of bag of marbles (bam) in Drosophila melanogaster, which plays a key role in germline stem cell daughter differentiation. Using RNA-seq, we find that W. pipientis infection in bam hypomorphic females results in differential expression of many of bam's genetic and physical interactors and enrichment of ubiquitination and histone lysine methylation genes. We find that W. pipientis also rescues the fertility and germline stem cell functions of a subset of these genes when knocked down with RNAi in a wild-type bam genotype. Our results show that W. pipientis interacts with ubiquitination and histone lysine methylation genes which could be integral to the mechanism by which W. pipientis modulates germline stem cell gene function.